Pengaruh Intervensi Peer Group terhadap Kemampuan Koping Anak yang Menghadapi Abuse dan Neglect - Yupi Supartini; Ratna Ningsih (Jurnal Keperawatan, 2018)
The purpose of this research to assess the influence of the peer group on coping abilities of teenagers who face abuse and neglect. Design studies used Quasi experiment. The population was children aged adolescents at high school, which was potentially facing abuse and neglect, in East Jakarta. The methode of sample selection was purposive sampling, determination of sample selection methdos have been due to a case of child abuse is a case that does not come to the surface/an iceberg phenomenon, so that a relatively small number reported. Methodes of data collection using questionnaires that have been tested. The results showed no significant effect of group therapy activities against child coping skills in the face of abuse and neglect (p value=0,019). The implications of this study can give an idea of how carers can provide care to children potentially exposed to violence and neglect, especially in school and can be input for health services, especially in health centers School health programs in designing the program in anticipation of or prevention of abuse and neglect in children school environment. This program provide feedback on the guidance counselor to develop a counseling program using a model of peer group. For the future studies it is advisabled to involve the parents as respondents.